Návrh komunikační strategie podniku - Svobodová, Martina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Diplomová práce, na základně provedené analýzy, navrhuje vhodnou komunikační strategii pro firmu poskytující sportovní služby. Komunikační strategie by měla vést ke zlepšení budoucího postavení na trhu a zvýšit podvědomí zákazníků o Sportcentru Holešov.

Based on the perfomed analysis, my graduation thesis offers a suitable communication strategy for company offering sporting services. The new communication strategy shall improve the future market position of the company and make customers more aware of the existence of the Sport Centre in Holešov.
Proposal of company strategic communication
Keywords: komunikační strategie; marketing; marketingový mix "7P"; komunikační mix; strategic communication; marketing; marketing mix "7P"; communication mix